National Health Insurance Scheme dispensing outreach and maintenance of health status In Oyo State (2013)
This study examined the dispensing outreach programme of the National Health Insurance Scheme (NHIS) and its influence on the health status of users. It specifically examined the influence of the organizational structure of NHIS on the referral process in the utilization of health care services by clients, documented the satisfaction client’ derived from NHIS service. It adopted a descriptive survey design through the use of qualitative and quantitative methods of data collection with four hundred and thirty-five enrollees. Sixteen In-depth interview was conducted with representatives of Health care International at Ibadan office. Data was analysed using the descriptive approach (method while qualitative data from the key informant interviews was content analyzed. Approximately 80% of the respondents preferred the NHIS services because it reduces the out-of-pocket expenses borne by the service users. Motivation for use of NHIS services stemmed from perceived services quality, drug availability, sophisticated pharmacy and the laboratory equipment. In terms of service expectation 57.1% of the respondents had their desires met as NHIS bore the bulk of health care cost, subsidized drugs and laboratory fees. Sixty percent of the studied population were thus satisfied with NHIS services though a reasonable proportion of 40% were dissatisfied with the way and manner their challenges were handled. Also, dissatisfying issues were associated with the delay in processing authorization code by Health Management Organization (HMO) when respondents were referred to secondary or tertiary health facility. The study recommended among others that government should improve on existing measures such as effective monitoring of the scheme implementation, facilitate the processing of authorization codes, ensure equity in access of all enrollees and the enforcement of adequate medical personnel and equipment for effective service delivery.